2000
DOI: 10.4049/jimmunol.165.8.4239
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of Human CD8+ T Cell Clones by Ectopic Expression of Telomerase Reverse Transcriptase

Abstract: Replicative senescence of T cells is correlated with erosion of telomere ends. Telomerase plays a key role in maintaining telomere length. Therefore, it is thought that telomerase regulates the life span of T cells. To test this hypothesis, we have over-expressed human telomerase reverse transcriptase in human CD8+ T cells. Ectopic expression of human telomerase reverse transcriptase led to immortalization of these T cells, without altering the phenotype and without loss of specificity or functionality. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 39 publications
11
127
1
3
Order By: Relevance
“…Although ectopic hTERT expression prevents telomere erosion and facilitates proliferation in some cell types without induction of transformation, [5][6][7][8][9][10] it has been reported that mice with transgenic expression of mouse TERT are susceptible to tumor development. 42 To some extent, telomerase activity may be associated with tumor development as some tumor cells show elevated telomerase activity and can still maintain long telomeres without pronounced telomerase activity.…”
Section: Ectopic Telomerase Expression Does Not Lead To Growth Transfmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ectopic hTERT expression prevents telomere erosion and facilitates proliferation in some cell types without induction of transformation, [5][6][7][8][9][10] it has been reported that mice with transgenic expression of mouse TERT are susceptible to tumor development. 42 To some extent, telomerase activity may be associated with tumor development as some tumor cells show elevated telomerase activity and can still maintain long telomeres without pronounced telomerase activity.…”
Section: Ectopic Telomerase Expression Does Not Lead To Growth Transfmentioning
confidence: 99%
“…4 Ectopic hTERT expression in various human cell types including T lymphocytes reconstitutes telomerase activity, prevents telomere erosion and extends the life span of these cells without altering their functional and phenotypic properties. [5][6][7][8][9][10] Although antigen-specific T cells are rescued from apoptosis during primary activation by telomerase expression, repeated antigenic stimulation leads to telomere shortening due to the loss of telomerase inducibility. 11,12 T-cell memory erosion has an important role in chronic infections related to severe pathology, especially in elderly individuals and in immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Trois études indépendantes ont récemment décrit l'introduction de hTERT et sa surexpression dans des lymphocytes T humains par l'emploi de vecteurs rétroviraux [19][20][21]. Deux types de cellules T ont été utilisées: des populations polyclonales de lymphocytes T CD8 + et des clones de cellules T, dérivés d'une seule cellule à partir de populations polyclonales.…”
Section: Controverses Dans L'immortalisation Des Lymphocytes T Humainsunclassified
“…Ainsi, une de ces publications montre que l'expression ectopique de hTERT stabilise la longueur des télomères, mais n'est pas suffisante pour immortaliser des cultures polyclonales de lymphocytes T [20]. En revanche, en utilisant des clones de cellules T, les deux autres études réussissent à prolonger significativement la durée de vie des lymphocytes tout en conservant un caryotype et un phénotype cellulaire normal (Figure 1) [19,21]. Une des explications serait que les conditions de culture (pour les populations polyclonales) soient inadéquates et induisent un stress non lié à la sénes-cence des cellules.…”
Section: Controverses Dans L'immortalisation Des Lymphocytes T Humainsunclassified
See 1 more Smart Citation